(3UjZ GdYbhO hGdEjbGYGJs - (3GdcQcj, GdYGedj, CHh GdMSf, GdeMbb GdKGfj, Ydj Hf GdMSjf Hf YHO GdYGdj, J (B940 (3g`s ((3eMeO Hf aQL Gddg Hf ESeGYjd Hf Ydj Gdfaj GdJHQjRj GdaQhjs)
(3ChdgG (B:s
(3GdMeO ddg (B...(3agPg LedI cGadI HHjGf UjZ GdYahO hGdEjbGYGJ EP cGf dGHO ef eYQaJgG def GMJGL Edi TjA efgG ef Gdecdajf dJhba MUhd GdGehQ GdeWdhHI efgG TQYG Ydi GdEJjGf HgG Ydi GdhLg GdeYJHQ (B...s
(3BNQgG (B:s
... (3hdh CHge GdEbQGQ aj TjFjf WhdH HGdHjGf hdh CbQ HdaX eHge agh GfhGY hdh GSJKfi ef GdbQHI adg CbSGe hCMcGe hLejY Pc ePchQ aj ebGeg ef cJH GdCUMGH QMege Gddg JYGdi ajWdH ef gfGc hdjcf gPG BNQ GdQSGdI (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B4/281s
(3GdPQjYI (B15 - 79( 732)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis